Дескриптивний аналіз лінгво-культурного типажу з соціальною домінантою «чиновник» у художньому дискурсі - Сукаленко, Тетяна Миколаївна (Хмельницька гуманітарно-педагогічна академія та Інститут літератури імені Т.Г. Шевченка Національної академії наук України, 2020)
У статті проаналізовано поняттєві та образно-перцептивні характеристики канцелярських, судових і поштових чиновників, представлених в українській літературі ХІХ ст. Класифіковано чиновництво за такими групами: канцелярські чиновники (канцелярист, секретар, реєстратор, столоначальник, письмоводитель, секретар, писар); судові чиновники – суддя, підсудок, писар в земському суді, секретар суду; поштові чиновники. Встановлено, що в описі канцелярських чиновників релевантними є зовнішні, внутрішні моральні, мовні та релігійні характеристики. Акцентовано увагу на внутрішніх моральних характеристиках судових чиновників ХІХ ст., провідними рисами яких були схильність до доносів і хабарництво. Закцентовано увагу на описі поштових чиновників, представлених у творах підавстрійських письменників, які зображені як активні учасники виборів, політичного життя.

The article deals with the analysis of the conceptual and figurative-perceptional characteristics of stationery, court and postal officials presented in the Ukrainian literature of the nineteenth century. As the material for the description of the type we used different fictional discourse of the XIX century (prose, dramatic, poetical, etc.) of Ukraine under Russian and Avstrian governing. We emphasised in the work that the linguocultural type is one of the special kinds of linguocultural concepts, the most important characteristics of which are motivated by the typicality of certain personality, its significance for the certain linguoculture. Due to the established approaches to the description of the concepts in the structure of linguocultural types, their conceptual, figurative-perceptive components are consistently revealed. The officials are classified in the following groups: office officials (stationery, secretary, registrator, stolonachalnyk, clerck, scribe); court officials - judge, judge assistant, scribe in zemskyi court, secretary of the court; postal officials. It has been found out that there are actual external, internal moral, lingual and religious characteristics in the description of officers. The attention is focused on the internal moral characteristics of court officials of the nineteenth century, the leading features of which there were the tendency to denunciations and bribery. It is emphasised that in the fictional discourse of the nineteenth century the lingual characteristic of the type of « official» is important. Two types of officials are represented here: the first - the lowest – Ukrainian language-speaking; the second one - who lost the relationship with the native language and uses Russian. The attention is focused on the description of postal officials, represented in the works of the writers in Ukraine under the Austrian governing, which are depicted as active participants in the elections, political life.
Keywords: лінгвокультурний типаж «чиновник»; канцелярські чиновники; судові чиновники; поштові чиновники; поняттєві характеристики; образно-перцептивні характеристики; дескриптивний аналіз; linguocultural type «official»; office officials; court officials; postal officials; conceptual characteristics; figurative-perceptive characteristics; descriptive analysis